2019
DOI: 10.1080/10255842.2019.1644502
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of muscle and intervertebral disc force computations to variations in muscle attachment sites

Abstract: The current paper aims at assessing the sensitivity of muscle and intervertebral disc force computations against potential errors in modeling muscle attachment sites. We perturbed each attachment location in a complete and coherent musculoskeletal model of the human spine and quantified the changes in muscle and disc forces during standing upright, flexion, lateral bending, and axial rotation of the trunk. Although the majority of the muscles caused minor changes (less than 5%) in the disc forces, certain musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…The slippage force values reported in our work were significantly close to the reported physiological loads in the literature, which could explain the tether breakage in vivo. In a recent study, intervertebral disc reaction forces during a 30-degree lateral bending were reported as 453 N, 460 N, and 652 N on the T6/T7, T12/L1, and L4/L5, respectively [ 19 ]. In another study, disc compressive forces during a 30-degree lateral bending on T11/T12 and L4/L5 were reported as 100% and 130% of the body weight, respectively, which corresponds to approximately 320–750 N for a 10–20-year-old adolescent (average 32–58 kg weight) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slippage force values reported in our work were significantly close to the reported physiological loads in the literature, which could explain the tether breakage in vivo. In a recent study, intervertebral disc reaction forces during a 30-degree lateral bending were reported as 453 N, 460 N, and 652 N on the T6/T7, T12/L1, and L4/L5, respectively [ 19 ]. In another study, disc compressive forces during a 30-degree lateral bending on T11/T12 and L4/L5 were reported as 100% and 130% of the body weight, respectively, which corresponds to approximately 320–750 N for a 10–20-year-old adolescent (average 32–58 kg weight) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 , 17 , 18 ]. However, recent biomechanical studies investigating the loads on the spine show that the highest physiological loads reach only up to approximately 650 N on the L4/L5 level, which corresponds to only 52 MPa (assuming the loads are coinciding with the tether’s axis) [ 19 ]. Furthermore, recent studies have shown that a correction force of 150–200 N is sufficient to modify the asymmetrical compression in AIS patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reported values for K vary between 10 and 100 N/cm 2 ( Daggfeldt and Thorstensson, 2003 ; Hansen et al, 2006 ). In models of the lower back, most commonly values of 46 ( Bogduk et al, 1992 ; Stokes and Gardner-Morse, 1995 ; Christophy et al, 2012 ), 60 ( Arjmand and Shirazi-Adl, 2006a ), 90 ( Arshad et al, 2016 ), or 100 N/cm 2 ( Bruno et al, 2015 ; Bayoglu et al, 2019 ; Favier et al, 2021a ; Lerchl et al, 2022 ; Malakoutian et al, 2022 ) were assumed. Thus, we tested values of 46, 73, and 100 N/cm 2 for K , expected ≤ 1.0°, and that no muscle was fully activated by the TC.…”
Section: Methodsmentioning
confidence: 99%
“…Most validated and extensively used biomechanical spine models belong to either the musculoskeletal multibody (MB) ( de Zee et al, 2007 ; Christophy et al, 2012 ; Bruno et al, 2015 ; Senteler et al, 2016 ; Malakoutian et al, 2018 ; Bayoglu et al, 2019 ; Lerchl et al, 2022 ; Meszaros-Beller et al, 2023 ) or implicit finite element (FE) method ( Schmidt et al, 2006 ; Ayturk and Puttlitz, 2011 ; Dreischarf et al, 2014 ; Naserkhaki et al, 2018 ; Turbucz et al, 2022 ). Musculoskeletal MB models are used to analyze mechanisms consisting of rigid bodies subject to mechanically simplifying joints and constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation